The significance of variations in immunoreactive and clottable fibrinogen in health and following thrombosis - Wolf, P. (1972)
In individuals in a steady state of fibrinogen metabolism, immunoreactive and clottable fibrinogen estimates of plasma fibrinogen show close agreement. These estimates also detect any increase of plasma fibrinogen (due to increased synthesis) following metabolic stresses but in certain circumstances discrepancies between immunoreactive and clottable fibrinogen values occur which are of diagnostic assistance. During extensive thrombosis, circulating `cryoprofibrin' (fibrin intermediates) may be formed. These fail to give full quantitative immunodiffusion reactions with antifibrinogen. Values for immunoreactive are therefore lower than for clottable fibrinogen. When intravascular catabolism (due to plasmin action) accompanies increased synthesis, since some of the molecular breakdown products of fibrin or fibrinogen react with antifibrinogen but are not clottable, immunoreactive values exceed those for clottable fibrinogen. This discrepancy is therefore an indicator of thrombolysis. Each discrepancy in turn may be encountered during the alternating predominance of thrombosis or thrombolysis in vivo: (a) physiologically, in association with the menstrual cycle; (b) pathologically, following surgical operations or extensive intravascular thrombosis.